Screening Emergency Admissions at Risk of Chronic Hepatitis C (SEARCH) to diagnose or 're‐diagnose' infections is effective in Australia. Issue 1 (21st September 2020) - Prince, David Stephen; Pipicella, Joseph Louis; Fraser, Melissa; Alvaro, Frank; Maley, Michael; Foo, Hong; Middleton, Paul MacConachie; Davison, Scott Anthony; Dore, Greg John; McCaughan, Geoff William; Levy, Miriam Tania
Abstract: The World Health Organization has set ambitious viral hepatitis elimination targets; however, difficulties in identifying and engaging patients remain. The emergency visit is an opportunity for enhanced linkage to care (LTC). We assessed the effectiveness of an automated Emergency Department (ED) screening service in identifying patients with hepatitis C (HCV) and achieving LTC. A retrospective evaluation was undertaken, analysing the first 5000 patients screened through an automatic Australian service termed 'Screening Emergency Admissions at Risk of Chronic Hepatitis' (SEARCH). Screening was performed for those recommended in the Australian national testing policy, specifically overseas born (OB) and Aboriginal or Torres Strait Islanders (ATSI). Healthcare worker education, patient information materials and opt‐out informed consent were used to test sera already collected for biochemistry assays. 5000 of 5801 (86.2%) consecutive eligible patients were screened (OB: 4778, ATSI: 222) from 14 093 ED presentations. HCV antibody was positive in 181 patients (3.6%); 51 (1.0%) were HCV RNA positive. Of 51 HCV RNA–positive patients, 12 were new diagnoses, 32 were ' re‐diagnoses ' (aware but lost to follow‐up [LTFU]), and 7 were previously known but treatment contraindicated. LTC was successful in 38 viraemic patients (7 deceased, 4 LTFU, 1 treatment ineligible and 1 declined). Of RNA‐negative patients, 75 were previously treated and 49 had presumed spontaneous clearance. Opt‐out consent was acceptable to all patients and staff involved. ED screening can lead to additional diagnosing and ' re‐diagnosing ' of HCV, with high rates of LTC. Opt‐out consent and automation removed major obstacles to testing.